2017
DOI: 10.1111/exd.13417
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic antimelanoma drugs suppress the activation of M2 macrophages

Abstract: Together with regulatory T cells (Tregs), tumor-associated macrophages (TAMs) play roles in maintaining the tumor microenvironment. Although cytotoxic antimelanoma drugs such as dacarbazine (DTIC), nimustine hydrochloride (ACNU) and vincristine (VCR) have been used for the treatment of malignant melanoma as adjuvant therapy in Japan, the detailed mechanisms of their immunomodulatory effects are not fully understood. As the majority of TAMs are alternatively activated M2 macrophages that favour tumor developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
(68 reference statements)
0
28
0
Order By: Relevance
“…We also evaluated other Th2 chemokines (CCL24 and CCL26) that might contribute to the pathogenesis of BP by the recruitment of eosinophils, and CCL2, which is reported to recruit the precursor of macrophages and is increased in the serum of BP patients . Minocycline and cyclosporine, respectively, significantly decreased the production of CCL2, CCL24 and CCL26 from M2 macrophages (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We also evaluated other Th2 chemokines (CCL24 and CCL26) that might contribute to the pathogenesis of BP by the recruitment of eosinophils, and CCL2, which is reported to recruit the precursor of macrophages and is increased in the serum of BP patients . Minocycline and cyclosporine, respectively, significantly decreased the production of CCL2, CCL24 and CCL26 from M2 macrophages (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…DPCP also led to nodal or visceral metastasis regression in four of the patients , thus suggesting the potential for an abscopal effect with this topically applied immunotherapy. A recent 2‐patient case series showed that topical immunotherapy has limited effect on internal disease, but that combined treatment with the PD‐1 inhibitor nivolumab led to pronounced internal metastasis regression . Within an ongoing trial treating melanoma patients with topical DPCP formulated in a non‐volatile, aqueous solvent as an Investigational New Drug (ClinicalTrials.gov number, NCT01711684), we have observed a remarkable tumor response in one patient on concurrent pembrolizumab therapy.…”
mentioning
confidence: 82%
“…Because the stromal factor on each cancer stem cell is an important factor for TAM stimulation, leading to the induction of specific TAM phenotypes, investigating the immunomodulatory stromal cells in the tumor microenvironment is important for establishing the appropriate immunotherapy for each type of cancer ( 1 , 8 , 9 , 16 , 17 ). In addition, it may be possible to repolarize TAMs into anti-tumor macrophages, such as M1-phenotype macrophages, to suppress tumor progression by modifying the profiles of tumor-infiltrating lymphocytes (TILs) ( 7 , 18 , 19 ). Thus, TAMs could be a target for immunotherapy in skin cancers ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%